Softening the agricultural matrix: a novel agri‐environment scheme that balances habitat restoration and livestock grazing. Issue 2 (1st November 2015) - Ansell, Dean; Fifield, Graham; Munro, Nicola; Freudenberger, David; Gibbons, Philip
Abstract : The loss and degradation of woody vegetation in the agricultural matrix represents a key threat to biodiversity. Strategies for habitat restoration in these landscapes should maximize the biodiversity benefit for each dollar spent in order to achieve the greatest conservation outcomes with scarce funding. To be effective at scale, such strategies also need to account for the opportunity cost of restoration to the farmer. Here, we critique the Whole‐of‐Paddock Rehabilitation program, a novel agri‐environment scheme which seeks to provide a cost‐effective strategy for balancing habitat restoration and livestock grazing. The scheme involves the revegetation of large (minimum 10 ha) fields, designed to maximize biodiversity benefits and minimize costs while allowing for continued agricultural production. The objectives and design of the scheme are outlined, biodiversity and production benefits are discussed, and we contrast its cost‐effectiveness with alternative habitat restoration strategies. Our analysis indicates that this scheme achieves greater restoration outcomes at approximately half the cost of windbreak‐style plantings, the prevailing planting configuration in southeastern Australia, largely due to a focus on larger fields, and the avoidance of fencing costs through the use of existing farm configuration and infrastructure. This emphasis on cost‐effectiveness, the offsetting of opportunity costs through incentive payments, and the use of a planting design that seeks to maximize biodiversity benefits while achieving production benefits to the farmer, has the potential to achieve conservation in productive parts of the agricultural landscape that have traditionally been "off limits" to conservation.